El gran Concepción: desarrollo histórico y estructura urbana primera parte génesis y evolución de las fundaciones militares a la conurbación industrial - Hernández Gurruchaga, Hilario (Investigaciones Geográficas: Una mirada desde el sur, 1983)
This article attemps to identify the characteristes and demographic-economic-social trends at spaces which conform. The Great Concepcion connurbated area (it is the thirst Chilean Metropolitan area) throught the study of the genesis and evolution of the urban units (first part) and integrant fluxes and relationships (second part). In the formative and transformative process, the author distinguishes three urbanization stages, which, with their regional particularities, respond to stimulus encouraged for national development stages. 1550-1830: lnitial stage, on which territorial hispanic domination purposes are setting to a regional level up through an early urban genesis, following for two longer centuries of slow economic and urban development, mainly because location at the war frontier. 1830-1930: On colonial earlier cities is overimposed an urban-economic new stage meaning growing and readecuation of the system. ln this expansive context and following economic diversifications promoted by an open international exchange policy, new cities emerged with specific locational demands (wheat ports and coal settlements): the initial advantages of early settlements as Concepcion and Talcahuano are developed and renewed, readecuating their size and functions to the communication changes. At the wheat exportation decline (1910-1930), comercial ports on Concepcion shoreline equally decline. 1930-1970: Since 1930 and because the import substitution policy, early cities began an industrialization stage, developing an industrial connurbation located around Concepcion (the directional focus). Since 1950 and because the concentration of the more basic and dynamic industries around Talcahuano and simultaneouslly, the decline of traditional economic basis (textile and coal), produced the weakness of peripheric satelite cities (Tome, Lota and Coronel) pushing a concentration process of the regional growth and its economic and social areal differentiation: the industrial connurbation is now attempting its transformation in urban aglomeration.